The Utilization of Zakat Based on Qawa’id Fiqhiyyah as a Solution to the Issues of Illegal Online Loans - Rizki Hasanah; Agus Mukmin; Rachmiya Saputri; Peny Cahaya Azwari (Yayasan Payungi Smart Madani, 2025)
Illegal online loans have become a common solution for people facing emergency financial needs, particularly in relation to family economic challenges. As a way to address the growing number of gharimin (debtors), this study explores the utilization of zakat based on qawa'id fiqhiyyah as a potential solution to the illegal online loan problem. This study uses a library research methodology with a descriptive qualitative approach. The findings indicate that zakat, when based on qawa'id fiqhiyyah, has not been fully optimized as a solution for illegal online loans. Factors such as the unclear classification of gharimin within the seven asnaf categories defined in Islamic law contribute to this issue. The study identifies key principles that justify the distribution of zakat to victims of illegal online loans. First, Al-Masyaqqah Tajlibu At-Taysīr (difficulty invites ease) suggests that Islamic law allows for flexibility and relief in times of hardship. Second, the principle of darurah (necessity), which permits the relaxation of prohibitions in critical situations, applies to individuals burdened by illegal debt. Third, Dar' al-Mafāsid Muqaddam' ala Jalb al-Maṣāliḥ (prevention of harm takes precedence over the pursuit of benefits) emphasizes that the risks such as psychological stress, social stigma, and even suicide, should be mitigated by preventing further harm through zakat. Finally, the principle of Al-‘Ādah Muḥakkamah allows for the inclusion of social customs as a legal basis, provided they do not conflict with Islamic law. This research offers a novel approach by integrating zakat within the broader legal and social context to address the issue of illegal online loans in Indonesia. The study contributes to the literature by highlighting zakat as an underutilized resource in combating financial exploitation in the digital age, providing new insights into the intersection of Islamic financial principles and contemporary economic challenges